Strategic Leaks in First-Price Auctions and Tacit Collusion: The Case of Spying and Counter-Spying - Cuihong Fan; Byoung Heon Jun; Elmar G. Wolfstetter (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze strategic leaks due to spying out a rival's bid in a first-price auction. Such leaks induce sequential bidding, complicated by the fact that the spy may be a counterspy who serves the interests of the spied at bidder and reports strategically distorted information. This ambiguity about the type of spy gives rise to a non-standard signaling problem where both sender and receiver of messages have private information and the sender has a chance to make an unobserved move. Whereas spying without counterspy exclusively benefits the spying bidder, the potential presence of a counterspy yields a collusive outcome, even if the likelihood that the spy is a counterspy is arbitrarily small. That collusive impact shows up in all equilibria and is strongest in the unique pooling equilibrium which is also the payoff dominant equilibrium.
Keywords: L12; L13; L41; D43; D44; D82; 330; auctions; tacit collusion; espionage; second-mover advantage; signaling; incomplete information